Understanding students’ technical skills during transition from primary to secondary school - Mohd Fadzil, H.; Mohd Saat, R. (2013)
Students lack exposure in ‘hands-on’ activities at primary school lead to insufficient manipulative skills and they may carry this problem with them to secondary school. Although most of the pupils are able to adapt to their new learning environment, some found transition difficult and problematic. Thus, to confront these issues, an in-depth study was proposed. This study resulted from a longitudinal study which employed a qualitative research paradigm. The research involved 10 primary school students (Year Six) and they were interviewed again in secondary school (Form One). Students’ ability in handling thermometer, measuring cylinder, Bunsen burner and microscope were observed in order to get comprehensive insight of students’ manipulative skills. From the data analysis, five (5) dimensions emerged to describe the students’ manipulative skills which are: (1) technical skills, (2) operation of tasks, (3) management of time and workplace, (4) safety and precautionary measures, and (5) numeracy and technique of drawing specimen. However this paper only discuss on the aspect of technical skills.